Correlation of International Prostate Symptom Score and uroflowmetry parameters in patients with benign prostatic hyperplasia in Western Nepal - Sharma, Suman; KC, Hari Bahadur; Baral, Suman; Bhattarai, Ananda; Bajgain, Bipin (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: The relationship between subjective symptom scores and objective uroflowmetric parameters in benign prostatic hyperplasia (BPH) is still being discussed, and data from South Asia, particularly Nepal, remain sparse. This study sought to ascertain the correlation between the International Prostate Symptom Score (IPSS) and uroflowmetry parameters like maximum flow rate (Qmax) and average flow rate (Qave) in men with BPH attending a tertiary care center in Western Nepal. Methods: This is a hospital based, prospective cross-sectional study which enrolled 92 consecutive men aged ≥40 years with lower urinary tract symptoms (LUTS) secondary to benign prostatic hyperplasia (BPH). Ethical committee approval and informed written consent were obtained. IPSS was administered with assistance where necessary due to low literacy. Data were coded and entered using Microsoft Excel version 2010 and transferred into SPSS Version 25 for analysis. Results: The median age was 70 years. The mean IPSS was 22.86 ± 5.82, with 71.7% of patients having severe symptoms. The median Qmax was 11.5 ml/s, and Qave was 6.0 ml/s. Spearman’s correlation revealed a weak, non-significant negative correlation between IPSS and Q max (ρ = –0.139, p =0.186) and between IPSS and Qave (ρ = –0.132, p =0.210). Conclusions: In this cohort from Western Nepal, there was no significant correlation between subjective symptom severity and objective uroflowmetric parameters. IPSS and Qmax assess different aspects of BPH and should be utilized as complementary instruments rather than interchangeable substitutes.